South Park: Acts of the General Assembly relating to the same, and the collection of the assessments : decisions of the Supreme Court relating thereto : ordinances : synopsis of improvements (1875) p. 77 § 6 - (:unkn) unknown (General Publisher, 1875)
Prohibited carry of firearms, throwing stones, or other missiles within the park
--
Keywords: CARRY - CERTAIN PUBLIC PLACES